Gonadal development and spawning periodicity of the ark shell, Scapharca inaequivalvis (Bruguire, 1789) (Mollusca, Pelecypoda Arcidae) in Banate Bay, Iloilo. - Ledesma-Fernandez, Leah N. (University of the Philippines in the Visayas, 2004)
Sex ratio, size at sexual maturity, gonadal development and spawning periodicity of the ark shell, Scapharca inaequivalvis (Bruguiere 1789), in Banate Bay were investigated. Ark shells ranging from 16.95 -61.6 mm shell length were sampled monthly from January to May 2002 and weekly from June to December 2002. S. inequivalvis is a diocecious species but shows no apparent external dimorphism. The female gonad is usually orange in color while that of the male is cream. The sex ratio is 1M:1.34F. The minimum size observed at sexual maturity is 17.27 mm in the male and 18.58 in the female. Gametogenic activity is throughout the year with a peak in Jaunuary-February and a minor one in August. Examination of the histological sections of the gonad also showed that spawning continously occurs throughout the year with the major spawning period observed from September to December and a minor breeding period between March to May for females and March to June for the males. This major spawning period associated with the southwest monsoon and higher levels of land -derived inputs or flow of organic matter. Throughout the year there were developing, maturing, and redeveloping of the gonads. Both the ovarian and testicular were parallel indicating synchronous gonadal develoment. GSI and lunar cycle are not correlated but trend showed slightly higher GSI somewhere between the new moon and the first quarter moon phases. Examination and measurement of the oocytes showed that they have varied sizes and are of four groups - oogonia, primary, secondary, and mature or free oocytes. Mature oocytes with size ranging mostly between 20 - 30 um predominate in the gonads of ripe females and ready to be spawned.